What seems to be the problem? challenges in offering bibliotherapy services in the Greater Manila Area - Karamihan, Callista Ashley H.
The literature on bibliotherapy services in the Philippines is few and far between as is knowledge of existing or past programs in libraries and health care institutions. To understand why bibliotherapy is uncommon, this study aimed to describe the challenges faced by providers of bibliotherapy services while implementing the practice. This study was inspired by the work of Alex-Nmecha and Onifade’s study on bibliotherapy services in Nigeria and uses the integrated Promoting Action on Research Implementation in the Health Sciences (i-PARIHS) framework by Harvey and Kitson to identify specific factors that affect the implementation of bibliotherapy services.